Do Operating Cash Flows Improve Firm Performance? The Moderating Role of Bank Foreign Ownership - Utkirov, Samandar; Apandi, R Nelly Nur; Sofia, Alfira; Nuriddin, Javliev (Jurnal Akuntansi & Keuangan Unja, 2026)
This study examines the effect of operating cash flow on firm performance and the moderating role of bank foreign ownership. Despite extensive research on firm performance, prior studies have limited attention to how internal financial capacity interacts with external ownership mechanisms, particularly in emerging market contexts. This study employs a quantitative approach using secondary data obtained from the annual reports and financial statements of non-financial companies listed on the Indonesia Stock Exchange (IDX). The final sample comprises 428 firm observations selected through purposive sampling. Multiple linear regression analysis is used to test the proposed hypotheses. The results indicate that operating cash flow has a positive and significant effect on firm performance, suggesting that firms with stronger operational cash generation tend to achieve better financial outcomes. Furthermore, the findings reveal that bank foreign ownership significantly moderates the relationship between operating cash flow and firm performance in a negative direction, indicating that the positive impact of operating cash flow on firm performance becomes weaker in firms with higher levels of foreign ownership. These results highlight the importance of internal financial capability and ownership structure in shaping firm performance in emerging markets.